Lithium-rich manganese-based oxides as positive electrode active materials for lithium-ion rechargeable batteries
The positive electrode active material for lithium-ion batteries, coated with Al or Zr, addresses the stability issues of lithium-rich manganese oxides by enhancing electrochemical stability and extending cycle life, achieving improved performance in lithium-ion batteries for electric vehicles.
Patent Information
- Application Number
- JP2024552461
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-03
- Filing Date
- 2023-03-03
- Publication Date
- 2025-03-21
AI Technical Summary
Lithium-rich and manganese-rich oxides used in lithium-ion secondary batteries for electric vehicles require charging above 4.5V to achieve high discharge capacity, leading to undesirable reactions with the electrolyte and transition metal dissolution, which reduces the long-term stability and cycling performance of the cathode material.
A positive electrode active material is developed, comprising Li, Mn, and oxygen, with a surface coating of Al or Zr, achieved through a method involving mixing, baking, drying, and an aluminum treatment step using atomic layer deposition, which enhances the electrochemical stability and extends the cycle life.
The surface-coated positive electrode active material exhibits improved electrochemical stability and extended cycle life, as indicated by a reduced capacity fading rate, compared to typical manganese oxides, effectively addressing the challenges of high operating potential and stability.
Smart Images

Figure 2025507968000012 
Figure 2025507968000013 
Figure 2025507968000014
Abstract
Description
[Technical field]
[0001] The present invention relates to a lithium manganese-based oxide positive electrode active material for lithium-ion secondary batteries (LIBs) suitable for electric vehicle (EV) and hybrid electric vehicle (HEV) applications, a method for producing the positive electrode active material, a battery including the positive electrode active material, and use of the battery. [Background technology]
[0002] With the rapid development of small and lightweight electronic products, electronic devices, communication devices, etc., and the growing need for electric vehicles to address environmental issues, there is a demand for improved performance of secondary batteries used as power sources for these products. Lithium and manganese rich oxides are attractive in terms of safety and energy density. However, these lithium and manganese rich oxides need to be charged above 4.5 V to reach a high discharge capacity of about 250 mAh / g. This high operating potential (>4.5 V) poses serious problems for the long-term stability of these cathodes due to unfavorable reactions of the electrodes with the electrolyte and dissolution of transition metals at the electrode-electrolyte interface. As a result, the cycle performance of the cathode materials is reduced.
[0003] Therefore, there is a need to mitigate the reaction between these cathodes and the electrolyte by modifying the surface of these cathodes, thereby further enhancing the cycle life of the cathode material.
[0004] It is an object of the present invention to provide positive electrode active materials having one or more improved properties, such as extended cycle life as indicated by capacity fading rate (QF) values in electrochemical cells.
[0005] It is a further object of the present invention to provide a method for producing a positive electrode active material.
[0006] It is a further object of the present invention to provide a battery including the positive electrode active material.
[0007] A further object of the present invention is to provide a use of said battery. Summary of the Invention [Means for solving the problem]
[0008] The object is to provide an active cathode material for a lithium-ion rechargeable battery, the active cathode material comprising Li, M' and oxygen, wherein M' is Mn with a content z of 40.0≦z≦90.0 mol% relative to M', Ni with a content x of 0.0≦x≦40.0 mol% relative to M', Co with a content y of 0.0≦y≦10.0 mol% relative to M', - M″ with a content b of 0.002≦b≦10.0 mol% relative to M′, D, the content c of which is 0.0≦c≦2.0 mol% relative to M′, wherein D contains an element other than Li, O, Ni, Co, Mn, and Al, - x, y, z, b, and c are measured by ICP-OES; -x+y+z+b+c is 100.0 mol%, This is accomplished by providing an active cathode material that includes secondary particles that include primary particles, the primary particles including an outer layer that includes M″, where M″ is Al, Zr, or a combination thereof.
[0009] The inventors have surprisingly found that by atomic layer deposition of Al2O3 and / or ZrO2, preferably Al2O3, onto Li-rich Mn-based oxide materials, the resulting cathode active material has an extended cycle life as indicated by the capacity fade rate (QF) value, as demonstrated in the accompanying examples, thereby extending the cycle life. The cathode comprising the cathode active material of the present invention exhibits improved electrochemical stability compared to cathodes comprising typical manganese-based oxides, due to the aluminum layer on top of the primary particles. Without wishing to be bound by any theory, the inventors believe that coating the surface of the cathode active material prevents direct contact with the electrolyte, thereby extending the cycle life of the cathode active material.
[0010] A further aspect of the present invention provides a method for producing an active cathode material, comprising the sequential steps of a mixing step, a first calcination step, a drying step, a second calcination step, and an aluminization step.
[0011] A further aspect of the invention provides a battery comprising the positive electrode active material.
[0012] A further aspect of the invention provides the use of a battery. [Brief description of the drawings]
[0013] [Figure 1] The Al distribution in EX2 measured by STEM-EDX is shown. [Diagram 2] 1 shows the thickness of the Al layer of EX2 measured by TEM. [Diagram 3] 1 shows the XPS profiles of the Al 2p peak of EX2 and EX3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] In order to enable the practice of the invention, preferred embodiments are described in detail in the drawings and the following detailed description. Although the invention has been described with reference to these specific preferred embodiments, it will be understood that the invention is not limited to these preferred embodiments. On the contrary, the invention encompasses numerous alternatives, modifications and equivalents, as will become apparent from a consideration of the following detailed description and the accompanying drawings.
[0015] The term "comprising" as used in the present specification and claims should not be interpreted as being limited to the means recited thereafter, nor does it exclude other elements or steps. It should be interpreted as specifying the presence of the recited features, integers, steps, or ingredients as mentioned, but without excluding the presence or addition of one or more other features, integers, steps, or ingredients, or groups thereof. Thus, the scope of the expression "a composition comprising components A and B" should not be limited to a composition consisting of components A and B only. It means that in the context of the present invention, the only relevant components of the composition are A and B. Thus, the terms "comprising" and "including" encompass the more restrictive terms "consisting essentially of" and "consisting of".
[0016] The positive electrode active material is defined as a material that is electrochemically active in the positive electrode, which is understood to be a material that can capture and release Li-ions when exposed to a voltage change for a certain period of time.
[0017] In the framework of the present invention, mol% means molar percentage. The expression mol% or "mole percent" of the concentration of a given element means what percentage of the total atoms in the compound concerned are atoms of that element. The expression mol% is equivalent to at% or atomic percentage.
[0018] positive electrode active material In a first aspect, the present invention provides an active cathode material for a lithium-ion rechargeable battery, the active cathode material comprising Li, M′, and oxygen, wherein M′ is Mn with a content z of 40.0≦z≦90.0 mol% relative to M', Ni with a content x of 0.0≦x≦40.0 mol% relative to M', Co with a content y of 0.0≦y≦10.0 mol% relative to M', - M″ with a content b of 0.002≦b≦10.0 mol %, preferably 0.2≦b≦10.0 mol %, relative to M′, D, with a content c of 0.0≦c≦2.0 mol% relative to M′, wherein D comprises elements other than Li, O, Ni, Co, Mn and M″, - x, y, z, b, and c are measured by ICP-OES; -x+y+z+b+c is 100.0 mol%, The active cathode material includes secondary particles that include primary particles, the primary particles including an outer layer that includes M″, where M″ is Al, Zr, or a combination thereof.
[0019] A highly preferred embodiment is the cathode active material of the invention where M″=Al.
[0020] Preferably, the Mn content z is greater than 50.0 mol% for M', preferably greater than 60.0 mol% for M', more preferably greater than 70.0 mol% for M'. Preferably, the Mn content z is less than 85.0 mol% for M', preferably less than 80.0 mol% for M', more preferably less than 75.0 mol% for M'. Preferably, the Mn content z is in the range 50.0≦z≦85.0 mol% for M', preferably in the range 60.0≦z≦80.0 mol% for M', more preferably in the range 70.0≦z≦75.0 mol% for M'.
[0021] Preferably, the Co content y is less than 9.0 mol% for M', preferably less than 8.0 mol% for M, preferably less than 7.0 mol% for M'. Preferably, the Co content y is greater than 0.5 mol% for M', preferably greater than 1.0 mol% for M', more preferably greater than 1.5 mol% for M'. Preferably, the Co content y is in the range 0.5≦y≦9.0 mol% for M', preferably in the range 1.0≦z≦8.0 mol% for M', more preferably in the range 1.5≦z≦7.0 mol% for M'.
[0022] Preferably, the Ni content x is less than 38 mol% for M', preferably less than 35 mol% for M', more preferably less than 30 mol% for M'. Preferably, the Ni content x is greater than 10 mol% for M', preferably greater than 15 mol% for M', more preferably greater than 20 mol% for M'. Preferably, the Ni content x is in the range of 10.0≦x≦38.0 mol% for M', preferably in the range of 15.0≦x≦35.0 mol% for M', more preferably in the range of 20.0≦x≦30.0 mol% for M'.
[0023] In a preferred embodiment, the content b is greater than 0.6 mol% for M', preferably greater than 0.7 mol% for M', more preferably greater than 0.8 mol% for M'. Preferably, the Al content b is less than 9 mol% for M', preferably less than 7 mol% for M', more preferably less than 6 mol% for M'. Preferably, the Al content b is in the range of 0.6≦x≦9.0 mol% for M', preferably in the range of 0.7≦x≦7.0 mol% for M', more preferably in the range of 0.8≦x≦6.0 mol% for M'. In a very preferred embodiment, the content b is greater than 0.5 mol% for M', preferably greater than 1.0 mol% for M', more preferably greater than 1.5 mol% for M'. Preferably, the content b is less than 5.0 mol% for M', preferably less than 3.0 mol% for M', more preferably less than 2.5 mol% for M'. Preferably, the content b is in the range of 0.5≦x≦5.0 mol % relative to M', preferably in the range of 1≦x≦3.0 mol % relative to M', and more preferably in the range of 1.5≦x≦2.5 mol % relative to M'.
[0024] In a highly preferred embodiment, M″=Al and the Al content b is greater than 0.6 mol% for M′, preferably greater than 0.7 mol% for M′, more preferably greater than 0.8 mol% for M′. Preferably, the Al content b is less than 9 mol% for M′, preferably less than 7 mol% for M′, more preferably less than 6 mol% for M′. Preferably, the Al content b is in the range 0.6≦x≦9.0 mol% for M′, preferably in the range 0.7≦x≦7.0 mol% for M′, more preferably in the range 0.8≦x≦6.0 mol% for M′. In a highly preferred embodiment, the Al content b is greater than 0.5 mol% for M', preferably greater than 1.0 mol% for M', more preferably greater than 1.5 mol% for M'. Preferably, the Al content b is less than 5.0 mol% for M', preferably less than 3.0 mol% for M', more preferably less than 2.5 mol% for M'. Preferably, the Al content b is in the range 0.5≦x≦5.0 mol% for M', preferably in the range 1≦x≦3.0 mol% for M', more preferably in the range 1.5≦x≦2.5 mol% for M'.
[0025] In one embodiment, M″=Zr and the Zr content b is greater than 0.002 mol% for M′, preferably greater than 0.003 mol% for M′, more preferably greater than 0.0035 mol% for M′. Preferably, the Al content b is less than 1 mol% for M′, preferably less than 0.5 mol% for M′, more preferably less than 0.1 mol% for M′. Preferably, the Zr content b is in the range of 0.002≦x≦1.0 mol% for M′, preferably in the range of 0.003≦x≦0.5 mol% for M′, more preferably in the range of 0.0035≦x≦0.1 mol% for M′.
[0026] In a preferred embodiment, D comprises at least one element from the group consisting of Zr, B, Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, Y, V, W, and Zn, preferably Zr, B, Cr, Nb, S, Si, Ti, Y, and W. In a more preferred embodiment, D consists of at least one element from the group consisting of Zr, B, Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, Y, V, W, and Zn, preferably B, Cr, Nb, S, Si, Ti, Y, and W.
[0027] Preferably, the D content c is greater than 0.25 mol% relative to M', preferably greater than 0.5 mol% relative to M', more preferably greater than 0.75 mol% relative to M'. Preferably, the D content c is less than 1.75 mol% relative to M', preferably less than 1.5 mol% relative to M', more preferably less than 1.25 mol% relative to M'. Preferably, the D content c is in the range of 0.25≦c≦1.75 mol% relative to M', preferably in the range of 0.5≦c≦1.5 mol% relative to M', more preferably in the range of 0.75≦c≦1.25 mol% relative to M'.
[0028] As will be appreciated by those skilled in the art, the amounts of Li and M', preferably Li, Ni, Mn, Co, D and M", preferably Al, in the positive electrode active material are measured by Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES). For example, and not limiting of the present invention, an Agilent ICP 720-ES is used in the ICP-OES analysis.
[0029] As will be understood by those skilled in the art, in the definition of the present invention, when the content of an element is stated using the symbol "0.0≦", this means that the presence of that element is optional.
[0030] In a preferred embodiment, the positive electrode active material is 3.5 μm 2 / g, preferably 3.7m 2 / g, more preferably 4.0m 2 In a preferred embodiment, the positive electrode active material has a specific surface area of more than 9.5 m 2 / g, preferably less than 8.5m 2 / g, more preferably less than 7.5m 2 In a preferred embodiment, the positive electrode active material has a specific surface area of 3.5 to 9.5 m 2 / g, preferably 3.7 to 8.5 m 2 / g, more preferably 4.0 to 7.5 m 2 In a highly preferred embodiment, the positive electrode active material has a specific surface area of 3.5 m 2 / g, preferably 6.5m 2 / g, more preferably 6.8m 2 In a highly preferred embodiment, the positive electrode active material has a specific surface area of greater than 9.5 m 2 / g, preferably less than 9.0m 2 / g, more preferably less than 8.5m 2 In a highly preferred embodiment, the positive electrode active material has a specific surface area of 3.5 to 9.5 m 2 / g, preferably 6.5 to 9.0 m 2 / g, more preferably 6.8 and 8.5m 2 / g. As will be understood by those skilled in the art, the specific surface area is measured by BET measurement. For example, but not limiting to the present invention, the specific surface area can be measured using a Micromeritics Tristar II 3020.
[0031] In a preferred embodiment, the atomic ratio of Li to M' (Li / M') is greater than 0.5, preferably greater than 1.0, more preferably greater than 1.1. In a preferred embodiment, the atomic ratio of Li to M' (Li / M') is less than 2.5, preferably less than 2.0, more preferably less than 1.6. In a preferred embodiment, the atomic ratio of Li to M' (Li / M') is 0.5 to 2.5, preferably 1.0 to 2.0, more preferably 1.1 to 1.6.
[0032] In a preferred embodiment, the cathode active material comprises secondary particles comprising a plurality of primary particles, the primary particles comprising an outer layer comprising Al, preferably Al2O3. As will be understood by those skilled in the art, the outer layer comprising Al is preferably coated on the primary particles of the cathode active material by the method of the second aspect of the present invention. As will be understood by those skilled in the art, the outer layer comprising Al can be measured by STEM-EDX and / or TEM, preferably TEM.
[0033] In one embodiment, the positive electrode active material comprises secondary particles comprising a plurality of primary particles, the primary particles comprising an outer layer comprising Zr, preferably ZrO2. As will be understood by those skilled in the art, the outer layer comprising Zr is preferably coated on the primary particles of the positive electrode active material by the method of the second aspect of the present invention. As will be understood by those skilled in the art, the outer layer comprising Zr can be measured by STEM-EDX and / or TEM, preferably TEM.
[0034] In the context of the present invention, the term "outer layer comprising M", preferably Al" means that the primary particles have an enriched amount of M", preferably Al, in the surface layer of the primary particles. In other words, the outer layer comprising M" is coated on the primary particles of the positive electrode active material. The outer layer may comprise other elements such as D resulting in an outer layer comprising M" and D.
[0035] As will be appreciated by those skilled in the art, a secondary particle comprises a plurality of primary particles, preferably more than 20 primary particles, preferably more than 10 primary particles, and most preferably more than 5 primary particles. Alternatively, as will be appreciated by those skilled in the art, a secondary particle comprises a plurality of primary particles, preferably more than 5 primary particles, preferably more than 10 primary particles, and most preferably more than 20 primary particles.
[0036] In a preferred embodiment, the thickness of the outer layer containing M″ of the positive electrode active material is greater than 0.1 nm, preferably greater than 0.2 nm, more preferably greater than 0.25 nm. In a preferred embodiment, the thickness of the outer layer containing M″ of the positive electrode active material is less than 10 nm, preferably less than 5.0 nm, more preferably less than 3.0 nm. In a preferred embodiment, the thickness of the outer layer containing Al of the positive electrode active material is 0.1 to 10 nm, preferably 0.20 to 5.0 nm, more preferably 0.25 nm to 3.0 nm. Alternatively, but equally preferably, in a preferred embodiment, the thickness of the outer layer containing M″ of the positive electrode active material is greater than 0.1 nm, preferably greater than 0.2 nm, more preferably greater than 0.25 nm. In a preferred embodiment, the thickness of the outer layer containing M″ of the positive electrode active material is less than 3.0 nm, preferably less than 2.9 nm, more preferably less than 2.8 nm. In a preferred embodiment, the thickness of the Al-containing outer layer of the positive electrode active material is 0.1 to 3.0 nm, preferably 0.2 to 2.9 nm, and more preferably 0.3 to 2.8 nm.
[0037] In a very preferred embodiment, the thickness of the Al-containing outer layer of the positive electrode active material is greater than 0.1 nm, preferably greater than 0.2 nm, more preferably greater than 0.25 nm. In a preferred embodiment, the thickness of the Al-containing outer layer of the positive electrode active material is less than 10 nm, preferably less than 5.0 nm, more preferably less than 3.0 nm. In a preferred embodiment, the thickness of the Al-containing outer layer of the positive electrode active material is 0.1 to 10 nm, preferably 0.20 to 5.0 nm, more preferably 0.25 nm to 3.0 nm. Alternatively, but equally preferred, in a preferred embodiment, the thickness of the Al-containing outer layer of the positive electrode active material is greater than 0.1 nm, preferably greater than 0.2 nm, more preferably greater than 0.25 nm. In a preferred embodiment, the thickness of the Al-containing outer layer of the positive electrode active material is less than 3.0 nm, preferably less than 2.9 nm, more preferably less than 2.8 nm. In a preferred embodiment, the thickness of the Al-containing outer layer of the positive electrode active material is 0.1 to 3.0 nm, preferably 0.2 to 2.9 nm, and more preferably 0.3 to 2.8 nm.
[0038] In a highly preferred embodiment, the thickness of the Al-containing outer layer is 0.50 to 2.50 nm, preferably 1.50 to 2.50 nm, more preferably 1.60 to 2.0 nm.
[0039] Typically, the thickness of the outer layer comprising M”, preferably Al, of the positive electrode active material can be measured from a TEM image, more specifically, a TEM image of one or more primary particles having an outer layer comprising M”, preferably Al. The TEM image can be suitably analyzed using an image software analysis application program, such as ImageJ software. The nanometer scale can be converted to pixel scale using an analysis tool, such as ImageJ software. Typically, the thickness is measured using this tool by manually drawing two parallel lines along the two edges of the layer. In addition, a third line perpendicular to the previous line is typically added manually. This line typically allows the width of the deposit to be measured by placing a cursor that relates the number of pixels to the number of nanometers. This is repeated 10 times at several positions on the layer to reduce the uncertainty. The thickness is typically a guideline and is rounded up to the upper value in nanometers, except when it is less than 1 nm.
[0040] In a highly preferred embodiment, the positive electrode active material of the present invention has an Al content of Al A of
[0041]
number
[0042] In a preferred embodiment, the positive electrode active material of the present invention has a Zr content of Zr A of
[0043]
number
[0044] Manufacturing method In a second aspect, the present invention also provides a process for making a cathode active material, comprising: Step 0) Optional precursor roasting step: Optionally, a manganese-based transition metal carbonate is roasted in an O2 atmosphere or dry air at a temperature of 350 to 450°C for 1 to 20 hours; Step 1) Mixing step: homogeneously mixing a manganese-based transition metal carbonate, preferably the roasted manganese-based transition metal carbonate from step 0), with a lithium source to obtain a mixture; Step 2) First firing step: firing the mixture from step 1) at a temperature of 750°C to 900°C to obtain a first fired material; Step 3) a second firing step: firing the material from step 2) at a temperature of 650°C to 750°C to obtain a double fired material; step 4) aluminum treatment step: treating the dual-fired material from step 3) with an Al source or a Zr source, preferably an Al source, by an atomic layer deposition reaction to obtain a positive electrode active material.
[0045] In a preferred embodiment of the method, the manganese-based transition metal carbonate is a carbonate compound containing greater than 40.0 mol % manganese relative to the major elements nickel, cobalt, and aluminum.
[0046] In a preferred embodiment of the method, the Li source is lithium hydroxide, lithium carbonate, lithium sulfate, or a combination thereof.
[0047] In a preferred embodiment of the method, in step 1), the lithium source is added in an atomic ratio to the manganese transition metal carbonate such that Li to M' (L / M') is greater than 0.5, preferably greater than 1.0, more preferably greater than 1.1. In a preferred embodiment, the atomic ratio of Li to M' (L / M') is less than 2.5, preferably less than 2.0, more preferably less than 1.6. In a preferred embodiment, the atomic ratio of Li to M' (L / M') is between 0.5 and 2.5, preferably between 1.0 and 2.0, more preferably between 1.1 and 1.6.
[0048] As will be understood by the skilled person, the homogeneous mixing of the manganese-based transition metal composition with the lithium source is a dry mixing of the manganese-based transition metal composition in powder form with the lithium source in powder form, the mixture obtained in step 1) being essentially free of liquid, e.g. less than 5 wt. %, preferably less than 2.5 wt. %, more preferably less than 1 wt. %, based on the total weight of the mixture.
[0049] In a preferred embodiment of the present method, in step 2), the firing temperature is 780° C. to 850° C., preferably 785° C. to 825° C., more preferably 790° C. to 810° C. In a preferred embodiment of the present method, in step 2), the firing time is 1 hour to 100 hours, preferably 5 hours to 20 hours, more preferably 8 hours to 14 hours.
[0050] In a preferred embodiment of the present method, in step 3), the firing temperature is 675° C. to 725° C., preferably 680° C. to 720° C., and more preferably 690° C. to 710° C. In a preferred embodiment of the present method, in step 4), the firing time is 1 hour to 100 hours, preferably 5 hours to 20 hours, and more preferably 8 hours to 14 hours.
[0051] In a preferred embodiment of the method, an atomic layer deposition (ALD) reaction in step 4) is carried out to form an outer layer comprising Al on top of the primary particles. ALD utilizes a sequential reaction of an Al source with HO, preferably the Al source is tris(diethylamino)aluminum (TDEAA), aluminum triisopropoxide, trimethylaluminum (TMA), aluminum ethoxide, isopropoxydimethylaluminum, tris(dimethylamido)aluminum, hexakis(dimethylamino)dialuminum or a combination thereof, preferably trimethylaluminum (TMA). In a preferred embodiment of the invention, ALD is carried out at a temperature between 50°C and 250°C, preferably between 75°C and 175°C, more preferably between 100°C and 150°C. In a preferred embodiment of the invention, ALD is carried out under an atmosphere comprising or consisting of an inert gas, preferably the inert gas is Ar. In a preferred embodiment of the method, the ALD reaction is carried out under a pressure of 10 mbar to 1000 mbar, preferably 25 mbar to 100 mbar, more preferably 40 to 80 mbar, by an injection pulse of the Al source for 1 s to 60 s, preferably 10 s to 30 s, preferably 15 s to 25 s. In a preferred embodiment of the method, the exposure time of the Al source and H2O is 1 s to 150 s, preferably 25 s to 100 s, most preferably 50 s to 70 s. As will be appreciated by those skilled in the art, step 5) of the method of the present invention can be repeated several times (i.e., cycles) to increase the thickness of the outer layer containing Al. In a preferred embodiment of the method, the ALD reaction of step 5) is carried out over several cycles, for example 1 to 50 cycles, preferably 2 to 30 cycles, more preferably 8 to 14 cycles. The inventors have surprisingly found that by repeating this reaction several times, an Al layer of intentionally increased thickness can be formed on top of the primary particles constituting the positive electrode active material, resulting in a positive electrode active material with an extended cycle life as indicated by the capacity fade rate (QF) value.As will be appreciated by those skilled in the art, atomic layer deposition is a well-known coating technique for producing highly uniform thin films (Ritala M., et al., Chem. Vap. Deposition 5, 7 (1999)).
[0052] In a preferred embodiment of the method, an atomic layer deposition (ALD) reaction in step 4) is carried out to form an outer layer comprising Zr on top of the primary particles. ALD utilizes a continuous reaction of a Zr source with HO, preferably the Zr source is tetrakis(dimethylamido)zirconium(IV), zirconium 2-methyl 2-butoxide, tetrakis(diethylamido)zirconium(IV), tetrakis(ethylmethylamido)zirconium(IV) or a combination thereof, preferably tetrakis(dimethylamido)zirconium(IV) (TDMAZ). In a preferred embodiment of the invention, ALD is carried out at a temperature between 50°C and 250°C, preferably between 75°C and 175°C, more preferably between 100°C and 150°C. In a preferred embodiment of the invention, ALD is carried out under an atmosphere comprising or consisting of an inert gas, preferably the inert gas is Ar. In a preferred embodiment of the method, the ALD reaction is carried out under a pressure of 10 mbar to 1000 mbar, preferably 20 mbar to 100 mbar, more preferably 25 to 40 mbar, by injection pulses of the Zr source for 1 s to 60 s, preferably 5 s to 30 s, preferably 10 s to 25 s. In a preferred embodiment of the method, the exposure time of the Zr source and H2O is 1 s to 150 s, preferably 25 s to 100 s, most preferably 50 s to 70 s. As will be appreciated by those skilled in the art, step 5) of the method of the present invention can be repeated several times (i.e., cycles) to increase the thickness of the outer layer containing Zr. In a preferred embodiment of the method, the ALD reaction of step 5) is carried out over several cycles, for example, 1 to 50 cycles, preferably 2 to 30 cycles, more preferably 8 to 14 cycles. The inventors have surprisingly found that by repeating this reaction several times, a Zr layer of intentionally increased thickness can be formed on top of the primary particles constituting the positive electrode active material, resulting in a positive electrode active material with an increased cycle life as indicated by the capacity fade rate (QF) value. As will be appreciated by those skilled in the art, atomic layer deposition is a well-known coating technique for producing highly uniform thin films (Ritala M., et al., Chem. Vap. Deposition 5, 7 (1999)).
[0053] In a highly preferred embodiment, the cathode active material obtained in step 4) is an cathode active material according to the first aspect of the present invention.
[0054] battery In a third aspect, the present invention relates to a battery comprising an active cathode material according to the first aspect of the present invention.
[0055] In a preferred embodiment, the battery is a lithium-ion battery, preferably a lithium-ion rechargeable battery. Preferably, the battery comprises a positive electrode comprising the positive electrode active material according to the first aspect of the present invention, a negative electrode, an electrode and a separator.
[0056] In a preferred embodiment, the battery according to the present invention has a capacity fade rate (QF) of less than 30% per 100 cycles, preferably less than 25% per 100 cycles, more preferably less than 15% per 100 cycles. As will be appreciated by those skilled in the art, capacity fade rate is measured as described under section C2) of the Examples.
[0057] use In a fourth aspect, the present invention relates to the use of an active cathode material according to the first aspect of the present invention in a battery.
[0058] A preferred embodiment is the use of a positive electrode active material in a battery, preferably in a battery according to the third aspect of the invention, to increase the efficiency of the battery.
[0059] In a fifth aspect, the present invention relates to the use of a battery according to the third aspect of the invention in any one of a portable computer, a tablet, a mobile phone, an energy storage system, an electric vehicle or a hybrid electric vehicle, preferably in an electric vehicle or a hybrid electric vehicle. EXAMPLES
[0060] A) Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES) Analysis The amount of Li, Ni, Mn, Co, Al and Zr in the positive electrode active material powder is measured by inductively coupled plasma optical emission spectroscopy (ICP-OES) method by using an Agilent ICP 720-OES. 2 grams of powder sample is dissolved in 10 mL of high purity hydrochloric acid (at least 37 wt% HCl with respect to the total weight of the solution) in an Erlenmeyer flask. The flask is covered with glass and heated on a hot plate at 380 °C until the precursor is completely dissolved. After cooling to room temperature, the solution in the Erlenmeyer flask is poured into a 250 mL volumetric flask. The volumetric flask is then filled with deionized water up to the 250 mL mark and then homogenized thoroughly. An appropriate amount of the solution is taken out with a pipette and transferred to a 250 mL volumetric flask for the second dilution, and the volumetric flask is filled with internal standard and 10% hydrochloric acid up to the 250 mL mark and then homogenized. Finally, this 50 mL solution is used for ICP measurement.
[0061] B) Surface area analysis The specific surface area of the positive electrode active material is measured by the Bruanauer-Emmett-Teller (BET) method by using a Micromeritics Tristar II 3020. To remove the adsorbed species, the powder sample is heated at 300°C for 1 hour before the measurement under nitrogen (N2) gas. The dried powder is placed in a sample tube. The sample is then degassed at 30°C for 10 minutes. The nitrogen adsorption test is performed in the instrument at 77K. The m 2 The total specific surface area of the sample in units of / g is derived.
[0062] C) Scanning Transmission Electron Microscopy (STEM) and Energy Dispersive X-ray Spectroscopy (EDS) Analysis Electron microscopy images were obtained by lamellarizing the particles with an ultramicrotome to obtain cross-sectional images, and then measured by scanning transmission electron microscopy (STEM) and energy dispersive X-ray spectroscopy (EDS). Cross-sectional TEM lamellae of the particles with a thickness of 70 nm were prepared by an ultramicrotome LEICA UC 7. TEM and STEM were measured with a JEM-ARM200F cold FEG using a cold-type field emission source, the TEM imaging resolution was 1.9 Å point and 1.0 Å line, the STEM imaging resolution was 0.78 Å, and HAADF JEOL, BF JEOL, HAADF GATAN, and BF / DF GATAN were used as STEM detectors. Element distribution was detected by EDS using an SDD CENTURIO-X and by EELS using a GATAND GIF QUANTUM ER spectrometer.
[0063] D) X-ray photoelectron spectroscopy (XPS) analysis In the present invention, X-ray photoelectron spectroscopy (XPS) is used to analyze the surface of the positive electrode active material powder particles. In the XPS measurement, the signal is obtained from the top of the sample, i.e., the first few nanometers (e.g., 1 nm to 10 nm) of the surface layer. Therefore, all elements measured by XPS are contained in the surface layer.
[0064] For the surface analysis of the positive electrode active material powder particles, XPS measurements are performed using a Kratos Axis Ultra DLD spectrometer. Monochromatic Al Kα radiation (hν=1486.6 eV) is used. A wide survey scan is performed to identify the elements present on the surface, and then a high-precision narrow scan is performed for each identified element to measure the exact surface composition. The C1s peak with maximum intensity (or center) at a binding energy of 284.65 eV is used as the calibration peak position after data collection.
[0065] Curve fitting is performed with CasaXPS version 2.3.19PR1.0 using Shirley-type background processing and Scofield sensitivity coefficients. Fitting parameters are according to Table 1a. The lineshape GL(30) is the equation of a Gaussian / Lorentzian product with 70% Gaussian and 30% Lorentzian lines. LA(α,β,m) is the asymmetric lineshape, where α and β define the tail broadening and m defines the width of the peak.
[0066] [Table 1]
[0067] For the Mn and Co peaks, limits are set for each defined peak according to Table 2b. All relevant Ni3p peaks are not quantified.
[0068] [Table 2]
[0069] The surface content of Al or surface content of Zr measured by XPS is expressed as the atomic fraction of Al or Zr in the surface layer of a particle divided by the total content of Ni, Mn, Co, Al, and Zr in that surface layer, which is calculated as follows:
[0070]
number
[0071] E) Coin Cell Test E1) Coin cell fabrication For the preparation of the positive electrode, a slurry containing the positive electrode active material powder, conductive agent (Super P, Timcal), and binder (KF#9305, Kureha) in a weight ratio of 83:8.0:8.0 in a solvent (NMP, Mitsubishi) is prepared by a high-speed homogenizer. The homogenized slurry is spread on one side of an aluminum foil using a doctor blade coater with a gap of 230 μm. The foil coated with the slurry is dried in an oven at 120 °C and then pressed using a calendar tool. It is then dried again in a vacuum oven to completely remove the residual solvent in the electrode film. The coin cell is assembled in an argon-filled glove box. A separator (Celgard 2320) is placed between the positive electrode and a piece of lithium foil to be used as the negative electrode. 1M LiPF6 in EC / DMC (1:2) is used as the electrolyte and is dropped between the separator and the electrode. The coin cell is then completely sealed to prevent electrolyte leakage.
[0072] E2) Test method The test method is a conventional "constant cut-off voltage" test. Conventional coin cell testing in this invention follows the schedule shown in Table 2. Each cell is cycled at 25°C using a Toscat-3100 computer controlled galvanostatic cycling station (Toyo).
[0073] The schedule uses a 1C current definition of 160mA / g in the 4.6V to 2.0V / Li metal window range. The capacity fade rate (QF) is given by the following equation:
[0074]
number
[0075] [Table 3]
[0076] The invention is further illustrated by the following (non-limiting) examples. Comparative Example 1 CEX (COMPARATIVE EXAMPLE) 1 is prepared according to the following process. 1) Precursor roasting process: Ni 0.27 Co 0.02 Mn 0.71 The Mn-based transition metal carbonate precursor having the metal composition of is roasted at 400 °C for 10 h in an O2 atmosphere with a heating rate of 5 °C / min, and then naturally cooled to room temperature. 2) First mixing step: 100 grams of the roasted Mn-based transition metal carbonate, 4.16 grams of Li2SO4, and 41.77 grams of Li2CO3 are mixed uniformly in an industrial blending facility such that the molar ratio of Li to metal M' (M' is the total molar content of Ni, Mn, and Co) (Li / M') is 1.40. 3) First calcination step: The first mixture from step 2) is calcined in dry air atmosphere at 600°C (heating rate to 500°C is 5°C / min, next heating rate to 600°C is 1°C / min) for 12 hours, and then cooled naturally to room temperature. 4) Second mixing step: 100 grams of the first calcined material and 2.65 grams of Li2Co3 are mixed uniformly to make the molar ratio of Li to metal M″ (M″ is the total molar content of Ni, Mn, and Co) (Li / M″) 1.47. 5) Second calcination step: calcinate the second mixture from step 4) in a dry air atmosphere at 800°C (the heating rate to 800°C is 1.5°C / min) for 10 hours, and then naturally cool to room temperature. The second calcined material has a Na content of 0.60 wt% and a S content of 1.29 wt% based on the total weight of the second calcined material. 6) Third calcination step: The dried material from step 5) is calcined at 700°C for 10 hours under dry air atmosphere to obtain Li-rich Mn-based transition metal oxide material. The calcined powder is labeled as CEX1.
[0077] Comparative Example 2 CEX2 is prepared according to the following process. 1) Mixing step: The lithium-rich Mn-based oxide material CEX1 is uniformly mixed with 0.38 wt % Al2O3 relative to the total transition metal amount of the CEX1 powder. 2) Heating step: The mixture from step 1) is heated at 375°C for 10 hours under dry air atmosphere and then allowed to cool to room temperature. The heated powder is labeled as CEX2.
[0078] Examples 1 to 3 A cathode active material comprising primary particles with an Al2O3 layer on top is prepared by atomic layer deposition (ALD) reaction with lithium-rich Mn-based oxide material CEX1 (10 g) using trimethylaluminum (TMA) as the aluminum source. ALD is carried out at 100-150 °C under Ar flowing atmosphere. The TMA injection pulse is 20 s dose to a pressure of 50 mbar, and the H2O injection pulse is 15 s dose to a pressure of 50 mbar. The total exposure time of TMA and H2O is 60 s. The Al2O3 deposited cathode active materials EX (Example) 1, EX2, and EX3 are obtained after 6, 12, and 25 cycles of ALD, respectively.
[0079] Table 3 summarizes the chemical formula, Al treatment method, Al layer thickness, BET value, and electrochemical properties.
[0080] Example 4 and Comparative Example 5 Cathode active materials comprising primary particles with a ZrO2 layer on top are prepared by atomic layer deposition (ALD) reaction with lithium-rich Mn-based oxide material CEX1 using tetrakis(dimethylamido)zirconium(IV) (TDMAZ) as the zirconium source. ALD is carried out with 2 grams of CEX1 at 200 °C under Ar flowing atmosphere. TDMAZ injection pulses are three 5-second doses to a pressure of 30 mbar, and H2O injection pulses are three 2-second doses to a pressure of 30 mbar. The total exposure times of TDMAZ and H2O are 16 minutes each, the same as the purge time. ZrO2-deposited cathode active materials EX4 and EX5 are obtained after 5 and 10 ALD cycles, respectively.
[0081] Table 4 summarizes the chemical formula, thickness of the Al layer, BET value, and electrochemical properties.
[0082] Comparative Example 3 CEX3 is prepared according to the same method as EX2, except that in step 6) of the preparation method of CEX1, the second calcination material is calcined at 1100°C.
[0083] Table 5 summarizes the specific surface area and electrochemical properties of EX2 and CEX3.
[0084] [Table 4]
[0085] [Table 5]
[0086] [Table 6]
[0087] The cross section of EX2 and the distribution of Al in EX2 are shown in Figure 1. It can be clearly observed that Al is well distributed in the secondary particles of EX2, and Al covers not only the surfaces of the secondary particles but also the surfaces of the primary particles.
[0088] Figure 2 shows the cross section of EX2 and the Al outer layer of the primary particle. The thickness of the Al layer can be measured using ImageJ software. This tool converts the nanometer scale to pixel scale. Draw two parallel lines along the two edges of the layer. Then add a third line at right angles to the first. On this line, the width of the deposit can be measured by placing a cursor that relates the number of pixels to the number of nanometers.
[0089] Figure 3 shows the XPS profiles of the Al 2p peaks of EX2 and EX3. The positions of the Al 2p peaks of EX2 and EX3 are 74.00 eV and 73.97 eV, respectively. According to "Handbook of XPS, 1992, Moulder, JF", Al in EX2 and EX3 can be considered to exist in the form of Al2O3.
[0090] CEX1 is a lithium-rich Mn-based transition metal oxide material, and CEX2 is a lithium-rich Mn-based transition metal oxide material that has been Al-treated by a conventional dry coating process. In terms of physical properties, CEX1 and CEX2 have an average particle size of 6.60m, respectively. 2 / g and 6.99m 2 / g. However, CEX1 shows a capacity fade rate (QF) higher than 35% / 100 cycles, and CEX2 shows a QF much higher than 300% / 100 cycles, indicating poor electrochemical stability. EX1, EX2, and EX3, which have the characteristics of the cathode material according to the present invention, result in materials with improved QF of at most 21% / 100 cycles in an electrochemical cell.
[0091] The Zr-containing positive electrode active materials EX4 and EX5 were 6.40 m2 / g and 6.49m 2 / g specific surface area. B / Zr A The value is 5384.6, and the Zr of EX5 B / Zr A The value was 1000.0, which represents a higher presence of Zr on the surface of the secondary particles than the Zr content in the center of the secondary particles. The capacity fade factors (QF) of EX4 and EX5 were 22.78% and 28.59%, respectively, which represents an improvement in QF compared to CEX1, which has a QF of 38.8%.
[0092] CEX3 is a lithium-rich Mn-based transition metal oxide material with an ALD coating, but with a specific surface area of 0.94 m 2 / g, and the electrochemical properties are poor. The DQ2 of CEX3 is 206.1 mAh / g, which is much lower than the DQ2 of EX2, which is 240.6 mAh / g.
Claims
1. 1. A cathode active material for a lithium ion rechargeable battery, the cathode active material comprising Li, M′, and oxygen, wherein M′ is - Mn with a content z of 40.0≦z≦90.0 mol% relative to M', - Ni with a content x of 0.0≦x≦40.0 mol% relative to M'; - Co with a content y of 0.0≦y≦10.0 mol% relative to M′, - M" with a content b of 0.002≦b≦10.0 mol% relative to M', D, with a content c of 0.0≦c≦2.0 mol % relative to M′, where D comprises elements other than Li, O, Ni, Co, Mn, and M″, - x, y, z, b, and c are measured by ICP-OES; -x+y+z+b+c is 100.0 mol%, The positive electrode active material is 3.5 to 9.5 m 2 / g specific surface area The active cathode material includes secondary particles that include primary particles, the primary particles including an outer layer that includes M″, where M″ is Al, Zr, or a combination thereof.
2. 2. The positive electrode active material according to claim 1, wherein the atomic ratio of Li to M' (Li / M') is 0.5 to 2.5, preferably 1.0 to 2.0, and more preferably 1.1 to 1.
6.
3. The positive electrode active material according to claim 1 or 2, wherein M″ is Al.
4. Al content Al A but, [0010] and the positive electrode active material has an Al content of Al B and Al B is measured by XPS analysis, and Al B is expressed as a mole fraction relative to the sum of the mole fractions of Ni, Mn, Co, and Al, as measured by XPS analysis, and the ratio Al B / Al A >1, preferably Al B / Al A >5, preferably Al B / Al A The positive electrode active material according to claim 3, wherein the molecular weight is >20.
5. The cathode active material according to any one of claims 1 to 4, preferably according to claim 3 or 4, wherein D comprises at least one element from the group consisting of Zr, B, Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, Y, V, W, and Zn, preferably Zr, B, Cr, Nb, S, Si, Ti, Y, and W, and more preferably D consists of at least one element from the group consisting of B, Cr, Nb, S, Si, Ti, Y, and W.
6. The cathode active material according to any one of claims 1 to 5, wherein the outer layer has a thickness of 0.1 nm to 10.0 nm, preferably 0.2 nm to 5.0 nm, preferably 0.25 nm to 3.0 nm.
7. 7. The cathode active material according to claim 1, wherein the Mn content z is greater than 50.0 mol% relative to M', preferably greater than 60.0 mol% relative to M', preferably greater than 70.0 mol%.
8. The positive electrode active material according to any one of claims 1 to 7, wherein the Co content y is less than 9.0 mol% relative to M', preferably less than 8.0 mol% relative to M', more preferably less than 7.0 mol% relative to M'.
9. The positive electrode active material according to any one of claims 1 to 8, wherein the Al content b is greater than 0.6 mol% relative to M', preferably greater than 0.7 mol% relative to M', more preferably greater than 0.8 mol% relative to M'.
10. A method for producing a cathode active material, the method comprising the following successive steps: Step 1) uniformly mixing a manganese-based transition metal carbonate with a lithium source to obtain a mixture; step 2) calcining the mixture from step 1) at a temperature of 750°C to 900°C to obtain a first calcined material; step 3) calcining the first calcined material from step 2) at a temperature of 650°C to 750°C to obtain a double calcined material; step 4) treating the dual-fired material from step 3) with an Al source or a Zr source, preferably an Al source, via an atomic layer deposition reaction to obtain the positive electrode active material.
11. 11. The method of claim 10, wherein the manganese-based transition metal carbonate of step 1) is first subjected to a roasting step.
12. The method according to claim 10 or 11, wherein the positive electrode active material is according to claims 1 to 9.
13. A battery comprising the positive electrode active material according to any one of claims 1 to 9.
14. 14. The battery of claim 13, wherein the battery is a lithium ion rechargeable battery.
15. 15. Use of the battery of claim 13 or 14 in one of a portable computer, a tablet, a mobile phone, an energy storage system, an electric vehicle, or in a hybrid electric vehicle.
Citation Information
Patent Citations
Lithium-manganese multiple oxide, its production, lithium secondary cell active substance and lithium secondary cell
JP2001002421A